Effects of coffee and caffeine anhydrous intake during creatine loading - Trexler, E. T.; Smith-Ryan, A. E.; Roelofs, E. J.; Hirsch, K. R.; Persky, A. M.; Mock, M. G. (The Journal of Strength and Conditioning Research, 2016)
The purpose of this study was to determine the effect of 5 days of creatine (CRE) loading alone or in combination with caffeine anhydrous (CAF) or coffee (COF) on upper-body and lower-body strength and sprint performance. Physically active males (n = 54; mean ± SD; age = 20.1 ± 2.1 years; weight = 78.8 ± 8.8 kg) completed baseline testing, consisting of 1 repetition maximum (1RM) and repetitions to fatigue with 80% 1RM for bench press and leg press, followed by a repeated sprint test of five, 10-second sprints separated by 60-second rest on a cycle ergometer to determine peak power (PP) and total power (TP). At least 72 hours later, subjects were randomly assigned to supplement with CRE (5 g of CRE monohydrate, 4 times per day; n = 14), CRE + CAF (CRE +300 mg/d of CAF; n = 13), CRE + COF (CRE +8.9 g of COF, yielding 303 mg of CAF; n = 13), or placebo (PLA; n = 14) for 5 days. Serum creatinine (CRN) was measured before and after supplementation, and on day 6, participants repeated pretesting procedures. Strength measures were improved in all groups (p = 0.05), with no significant time × treatment interactions. No significant interaction or main effects were observed for PP. For TP, a time × sprint interaction was observed (p = 0.05), with no significant interactions among treatment groups. A time × treatment interaction was observed for serum CRN values (p = 0.05) that showed increases in all groups except PLA. Four subjects reported mild gastrointestinal discomfort with CRE + CAF, with no side effects reported in other groups. These findings suggest that neither CRE alone nor in combination with CAF or COF significantly affected performance compared with PLA.